PENGAWASAN CAMAT TERHADAP PEREDERAN MINUMAN BERALKOHOL DI KECAMATAN SENAPELAN KOTA PEKANBARU - Anggi Permana; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Pekanbaru city government that has the responsibility and authority to oversee alcoholic beverages, in line with government policy that puts districts as the city government, the mayor of Pekanbaru based on Decree No. 112 of 2012 on the transfer of part of the authority of government from mayor to the sub-district to sub-district number diserahkanlah affairs. One of the responsibilities that must be implemented by the sub-district is the field of industry, trade and investment which includes supervision over the distribution of alcoholic beverages.The purpose of this study is to investigate and analyze the sub-district Supervision Against Alcoholic Beverage Distribution in District Senapelan Pekanbaru and any factors that inhibit the process of monitoring the circulation of alcoholic beverages. This research was conducted in the District Senapelan Pekanbaru. The theory used in this study is the theory of supervision. In collecting the data obtained from in-depth interviews to the informant. Once the data is collected and then analyzed using qualitative descriptive analysis.After doing research, supervision of the traders who sell alcoholic beverages less than optimal. This is caused because the lack of activities raid, although there are only done once a year such as religious holidays. The resistance of the sub-district supervision of the circulation of alcoholic beverages in the District Senapelan Pekanbaru City is still limited to the District personnel conduct routine surveillance, lack of oversight by the sub-district. Suggestions to overcome these barriers need to be increased activity should raid for every shop that sells alcoholic beverages and a deterrent effect on retailer that is the catch.Keywords : Control District Head, Distribution of Alcoholic Beverages